The Effort of Improves CreativityFfree Child Age Group B Using Media Sand in PAUD Rianda Martubung Medan Labuhan - Rezeki, Ulfah Sari (Universitas Negeri Medan, 2017)
The problem in this research is about the not yet the development of the optimal child free drawing creativity. The purpose of this research is to improve the creativity of free drawing of early age group B using sand media in PAUD Rianda Martubung Medan Labuhan. The theory used in this research includes theories about free drawing creativity that discusses the ability of children in creating ideas / ideas, imagination / fantasy. The method used in this research is classroom action research conducted in 2 cycles, where each cycle consists of planning, implementation, observation and reflection. The subject of this research is group B PAUD Rianda Martubung Medan Labuhan. Number of children subject to 20 children consisting of 10 boys and 10 girls. To obtain the necessary data in this study used an observation sheet on the improvement of free drawing creativity. From the result of data analysis, the average value of children's free drawing creativity in the pre-cycle stage is 31.56%, in the first cycle the creativity of children free drawing is observed from the indicators of free drawing creativity such as imagination, ideas / ideas, confidence , diligent and tenacious, it has increased by 51.56% and in cycle II the average creativity of free drawing of children by using sand media has increased significantly to 82.5%, so it can be concluded that through the use of sand media can improve the creativity of drawing free early childhood group B PAUD Rianda Martubung Medan Labuhan.